Association between γ marker, human leucocyte antigens and killer immunoglobulin‐like receptors and the natural course of human cytomegalovirus infection: a pilot study performed in a Sicilian population. Issue 4 (11th December 2017) - Di Bona, Danilo; Accardi, Giulia; Aiello, Anna; Bilancia, Massimo; Candore, Giuseppina; Colomba, Claudia; Caruso, Calogero; Duro, Giovanni; Gambino, Caterina M.; Macchia, Luigi; Pandey, Janardan P.
Summary: Natural killer (NK) cells provide a major defence against human cytomegalovirus (HCMV) infection through the interaction of their surface receptors, including the activating and inhibitory killer immunoglobulin‐like receptors (KIRs), and human leucocyte antigen (HLA) class I molecules. Also γ marker (GM) allotypes, able to influence the NK antibody‐dependent cell‐mediated cytotoxicity, appear to be involved in the immunological control of virus infections, including HCMV. In some cases, their contribution requires epistatic interaction with other genes of the immune system, such as HLA. In the present report, with the aim of gaining insight into the immune mechanisms controlling HCMV, we have studied the possible associations among humoral and NK responses, and HCMV infections. In a previous study we assessed whether the KIR and HLA repertoire might influence the risk of developing symptomatic ( n = 60) or asymptomatic ( n = 60) disease after primary HCMV infection in the immunocompetent host. In the present study, the immunocompetent patients with primary symptomatic HCMV infection were genotyped for GM3/17 and GM23 allotypes, along with the 60 participants with a previous asymptomatic infection as controls. Notwithstanding the presence of missing data record, advanced missing data recovery techniques were able to show that individuals carrying the GM23 allotypes, both homozygous and heterozygous, GM17/17, HLA‐C2 and Bw4 T KIR‐ligand groups are associated with the risk of developing symptomatic infection. Our findings on the role of both cellular and humoral immunity in the control of HCMV infection should be of value in guiding efforts to reduce HCMV‐associated health complications in the elderly, including immunosenescence, and in transplantation. Abstract : In a previous study we assessed whether the killer immunoglobulin‐like receptors (KIR) and the human leucocyte antigen (HLA) repertoire might influence the risk of developing symptomatic or asymptomatic disease after primary human cytomegalovirus (HCMV) infection in the immunocompetent host. In the present study, immunocompetent patients with primary symptomatic HCMV infection were genotyped for GM3/17 and GM23 allotypes, along with the 60 participants with a previous asymptomatic infection as controls. Individuals carrying the GM23 allotypes, both in homozygosity and heterozygosity, GM17/17, HLA‐C2 and Bw4 T KIR‐ligand groups are associated with the risk of developing symptomatic infection.